2004
DOI: 10.1172/jci200419657
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of c-Jun signaling in regulation of NFAT family and RANKL-regulated osteoclast differentiation

Abstract: IntroductionThe amount of bone remodeling is controlled by the balance between bone formation and bone resorption (1-3). Many osteopenic diseases, including osteoporosis, rheumatoid arthritis, Paget disease, and lytic bone metastases of malignancies are characterized by progressive and excessive bone resorption by osteoclasts, which are multinucleated giant cells that originate from hematopoietic cells (2). A TNF family member, receptor activator of NF-κB ligand (RANKL), which is expressed as a membrane-bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
161
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 387 publications
(173 citation statements)
references
References 41 publications
(35 reference statements)
12
161
0
Order By: Relevance
“…Thus, it is not surprising, in retrospect, that RANKLinduced osteoclastogenesis involves partnering of Fos/Jun with NFAT2. The fact that Ikeda et al (1) found that expression of NFAT2 itself is NFAT1/Fos/Jun-dependent is in keeping with the presence of NFAT and AP-1 response elements in the NFAT2 promoter (19). Reflecting its role as an essential RANKL-activated signaling molecule, NFAT2, when overexpressed in wild-type macrophages, prompts osteoclast differentiation in the absence of the osteoclastogenic cytokine (17).…”
Section: Nfat and Ap-1 In 2002 Takayanagi Et Al Identified Nfat2mentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, it is not surprising, in retrospect, that RANKLinduced osteoclastogenesis involves partnering of Fos/Jun with NFAT2. The fact that Ikeda et al (1) found that expression of NFAT2 itself is NFAT1/Fos/Jun-dependent is in keeping with the presence of NFAT and AP-1 response elements in the NFAT2 promoter (19). Reflecting its role as an essential RANKL-activated signaling molecule, NFAT2, when overexpressed in wild-type macrophages, prompts osteoclast differentiation in the absence of the osteoclastogenic cytokine (17).…”
Section: Nfat and Ap-1 In 2002 Takayanagi Et Al Identified Nfat2mentioning
confidence: 87%
“…AMP-activated protein kinase (AMPK) is the downstream component of a protein kinase cascade that is highly conserved in all eukaryotic cells (1). AMPK is activated by the rising cellular AMP that (due to the action of adenylate kinase) always accompanies a fall in the cellular ATP/ ADP ratio, and this activation is antagonized by high concentrations of ATP (Figure 1).…”
mentioning
confidence: 99%
“…In contrast, RANKL-mediated JNK phosphorylation was retarded and reduced in the absence of PLCγ2 ( Figure 5B), and activation of c-Jun (by phosphorylation) was also decreased in both the cytoplasm and the nucleus ( Figure 5, B and C). This result is particularly compelling, since JNK/c-Jun activates the AP1 complex, and inhibition of JNK activity blocks RANKL-induced OC development (19). Thus, to determine whether the decreased phosphorylation of JNK observed in Plcg2 -/-BMMs stimulated with RANKL could result in deficient AP1 activation, nuclear extracts from WT and Plcg2 -/-cells were subjected to EMSA analysis following RANKL stimulation.…”
Section: Plcγ2 Is Required For Efficient Rankl-induced Activation Ofmentioning
confidence: 99%
“…Furthermore, overexpression of the WT protein stimulates OC development from embryonic stem cells in a RANKL-independent manner (18). Interestingly, the ability of NFATc1 to mediate osteoclastogenesis is strictly connected to the c-Jun pathway (19). Transgenic mice expressing a dominant negative form of c-Jun have osteopetrosis due to defective osteoclastogenesis that cannot be rescued by NFATc1 overexpression in OCs (19).…”
Section: Introductionmentioning
confidence: 99%
“…After retroviral transfer of DAP12 the osteopetrotic phenotype was rescued. The association of paired immunoglobulin-like receptor A (PIR-A) and OSCAR to FcRγ and triggering receptor expressed on myeloid cells (TREM) 2 and signal-regulatory protein β1 (SIRPβ1) to DAP12 in osteoclast precursors is considered to act as a co-stimulatory signal for RANKL, since one signal by its own is not able to induce osteoclastogenesis [156,157,158]. …”
Section: The Rankl/opg/rank Networkmentioning
confidence: 99%